2019
DOI: 10.1116/1.5085192
|View full text |Cite
|
Sign up to set email alerts
|

Thermal chemical vapor deposition of epitaxial rhombohedral boron nitride from trimethylboron and ammonia

Abstract: Epitaxial rhombohedral boron nitride films were deposited on α-Al2O3(001) substrates by chemical vapor deposition, using trimethylboron, ammonia, and with a low concentration of silane in the growth flux. The depositions were performed at temperatures from 1200 to 1485 °C, pressures from 30 to 90 mbar and N/B ratios from 321 to 1286. The most favorable conditions for epitaxy were: a temperature of 1400 °C, N/B around 964, and pressures below 40 mbar. Analysis by thin film X-ray diffraction showed that most dep… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(36 citation statements)
references
References 30 publications
3
33
0
Order By: Relevance
“…Comparing the pole figure of (011false¯2) Al 2 O 3 substrate (not shown), BN crystal lattice is found to be 30° in‐plane rotated with respect to Al 2 O 3 substrate. It indicates the crystal orientation relationship between BN and Al 2 O 3 is (0001) BN || (0001) Al 2 O 3 and [1true1¯00 ] BN || [11true2¯0] Al 2 O 3 , which agree with CVD‐grown BN films …”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…Comparing the pole figure of (011false¯2) Al 2 O 3 substrate (not shown), BN crystal lattice is found to be 30° in‐plane rotated with respect to Al 2 O 3 substrate. It indicates the crystal orientation relationship between BN and Al 2 O 3 is (0001) BN || (0001) Al 2 O 3 and [1true1¯00 ] BN || [11true2¯0] Al 2 O 3 , which agree with CVD‐grown BN films …”
Section: Resultssupporting
confidence: 59%
“…Many research groups have reported BN growth by thermal chemical vapor deposition (CVD), plasma‐assisted CVD, and molecular beam epitaxy (MBE) . The growth conditions include a wide varieties of boron precursors of borazine (B 3 N 3 H 6 ), boron halides (BF 3 , BCl 3 , BBr 3 ), triethylboron ((C 2 H 5 ) 3 B, TEB), trimethylboron ((CH 3 ) 3 B, TMB), and diborane (B 2 H 6 ) . Also, various substrates for BN growth were investigated, such as sapphire, SiC, Ni, and Cu …”
Section: Introductionmentioning
confidence: 99%
“…However, deposition of crystalline sp 2 -BN films by thermal CVD often requires deposition temperatures above 1200 °C. [2][3][4][5][6][7][8][9] This limits the choice of substrate materials for epitaxy seen from demonstrated growth on 3C-SiC(111), 4H-and 6H-SiC(0001) and Al2O3(0001).…”
Section: Introductionmentioning
confidence: 99%
“…Epitaxial growth of sp 2 -BN by chemical vapor deposition (CVD) has been demonstrated on 3C-SiC(111), 4H-and 6H-SiC(0001) on-axis substrates and α-Al 2O3(0001) at temperatures above 1200 °C [11][12][13][14][15] . However, these substrates require surface pre-treatment to support nucleation of BN, where controlled graphitization 16 or ramping up in a SiH4-H2 ambient 13 was needed on SiC substrates while controlled nitridation to form AlN supported growth on α-Al2O3(0001) substrates 11,17 .…”
Section: Introductionmentioning
confidence: 99%